Long‐Lived Foams Stabilized by a Hydrophobic Dipeptide Hydrogel. Issue 3 (30th November 2015) - Li, Tao; Nudelman, Fabio; Tavacoli, Joe W.; Vass, Hugh; Adams, Dave J.; Lips, Alex; Clegg, Paul S.
Abstract : A hydrogel of hydrophobic dipeptides can be used to create a wet foam with long‐term stability. The dipeptide molecules self‐assemble into fiber‐like networks (due to the presence of metal ions) both at air–water interfaces and in the continuous phase. The former creates an interfacial film stabilizing the air bubbles while the latter forms a bulk gel, which prevents bubble movement and retards growth. If the storage modulus (G′) of the bulk hydrogel is sufficiently high it can stop the coarsening of the air bubbles and thus dramatically improve the stability of the foam. Cryogenic scanning electron microscopy and Raman spectra reveals the width of the fibers (200 nm) and that they are held together by hydrogen bonds. In the absence of bubbles, phase separation is observed between a hydrogel and a water‐rich phase; in the foam this can be suppressed provided that the concentration of dipeptides and metal ions are sufficiently high. It is speculated that the resistance of the bubble arrangement to compaction and hence further drainage arrests the process of phase separation. This foam system has the advantages of long stability, low cost, as well as easy preparation; therefore, it has potential applications in food manufacturing, drug delivery, and personal care industries. Abstract : A wet foam system with long‐term stability can be prepared using a hydrophobic dipeptide hydrogel. The dipeptide molecules preferentially self‐assemble into interfacial films to protect the air bubbles. Excess molecules form a 3D network in the continuous phase, which reduces drainage and suppresses bubble coarsening. The concentration and storage modulus of the hydrogel can affect the foam stability.